Through a Hazy Lens: A Teen’s Surprising Struggle with Juvenile Cataracts - Imelda, Eva; Jannah, Siti Rain; Annisa, Thyfa; Adev, Sarra Mutiara; Toshniwal, Navneet Shamsundar (Indonesian Journal of Case Reports, 2024)
A juvenile cataract is a condition in which the eye's lens gets cloudy, affecting children and teenagers and considerably impairing vision. It accounts for approximately 5% to 20% of childhood blindness worldwide. A 16-year-old male patient came with his parents to the Pediatric Ophthalmology and Strabismus Department of RSUD dr. Zainoel Abidin with complaints of blurred vision in both eyes. The patient admitted that his visual acuity was deteriorating, and he had difficulty seeing the blackboard when the teacher explained it at school. There were no factors that aggravated or relieved the patient's complaints. The ophthalmologic examination showed the visual acuity of both eyes was 6/30, and the bilateral lenses were opaque. The patient was diagnosed with juvenile cataract oculi dextra et sinistra. Subsequently, the patient was planned for aspiration irrigation with intraocular lens (IOL) insertion in both eyes, membranectomy, primary posterior capsulectomy (PPC), and anterior vitrectomy (AV). Following the surgery, the visual acuity of both his eyes was improved to 6/7 and 6/10. The patient was also prescribed oral and topical antibiotics and topical anti-inflammatories to prevent infection and persistent inflammation after surgery. After surgery, the patient was also planned for optical rehabilitation one month postoperatively by being prescribed glasses with the best correction of 6/6 in both eyes.